Physical Stability Profile Of Curcuma xanthorrhiza Roxb Extract Gel With Various Carbomer® 940 Concentration - Jainer Pasca Siampa, Abdul Halim Umar, Muhammad Afif (Jurnal Farmasi dan Ilmu Pengobatan, 2016)
Curcuminoid is a compound contained in turmeric (Curcuma xanthorrhiza Roxb) that act as antioxidants, anti-inflammatory, hepatoprotective and antibacterial. This research aimed to obtain a gel formula from ethanol extract of Curcuma xanthorrhiza Roxb that has good physical stability by using Carbomer® 940 as a gelling agent. Gel made in six formulas with extract and various concentration of Carbomer® 940 and evaluated physically such as organoleptic, homogeneity, viscosity, pH, spreading power, and adhesion before and after accelerated test. The data were analyzed using paired T-test. The result showed that formula 6 with 2% Carbomer is the best and physically stable before and after the stress condition. Formula 6 showed a homogeny gel with brownish yellow color, specific odor, texture soft and viscous. The value of viscosity, pH, spreading power, and adhesion respectively was 185,000 mPas; 6.8; 6.8 cm; and 44.16 seconds